Statistical methods for modelling neural networks - Marcelo C. Medeiros; Timo Terasvirta (Pontifícia Universidade Católica do Rio de Janeiro (PUC-Rio), Departamento de Economia, 2001)
In this paper modelling time series by single hidden layer feedforward neural network models is considered. A coherent modelling strategy based on statistical inference is discussed. The problems of selecting the variables and the number of hidden units are solved by using statistical model selection criteria and tests. Misspecification tests for evaluating an estimated neural network model are considered. Forecasting with neural network models is discussed and an application to a real time series is presented.
Keywords: C22; C51; C52; C61; G12; 330